2002
DOI: 10.1097/00004714-200208000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Risperidone Metabolism by Fluoxetine in Patients With Schizophrenia: A Clinically Relevant Pharmacokinetic Drug Interaction

Abstract: The effect of fluoxetine on the steady-state plasma concentrations of risperidone and its active metabolite 9-hydroxyrisperidone (9-OH-risperidone) was evaluated in 10 patients with schizophrenia or schizoaffective disorder. Patients stabilized on risperidone (4-6 mg/day) received additional fluoxetine (20 mg/day) to treat concomitant depression. One patient dropped out after 1 week due to the occurrence of akathisia associated with markedly increased plasma risperidone concentrations. In the other subjects, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 29 publications
1
54
0
2
Order By: Relevance
“…However, these combinations may result in clinically relevant pharmacokinetic interactions as a consequence of the differential inhibitory effects of SSRIs on CYP enzymes [25]. In this respect, formal kinetic studies in patients with schizophrenia have reported that paroxetine and fluoxetine increased plasma concentrations of risperidone active moiety by 45 and 75%, respectively, sertraline caused a minimal, dose-dependent elevation of total risperidone concentrations, while citalopram did not modify significantly the plasma levels of risperidone and its metabolite [10,11,26,27]. With regard to other newer antidepressants, reboxetine and mirtazapine do not cause significant modifications of plasma concentrations of risperidone active fraction [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these combinations may result in clinically relevant pharmacokinetic interactions as a consequence of the differential inhibitory effects of SSRIs on CYP enzymes [25]. In this respect, formal kinetic studies in patients with schizophrenia have reported that paroxetine and fluoxetine increased plasma concentrations of risperidone active moiety by 45 and 75%, respectively, sertraline caused a minimal, dose-dependent elevation of total risperidone concentrations, while citalopram did not modify significantly the plasma levels of risperidone and its metabolite [10,11,26,27]. With regard to other newer antidepressants, reboxetine and mirtazapine do not cause significant modifications of plasma concentrations of risperidone active fraction [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that co-administration of CYP2D6 inhibitors or CYP3A4 inhibitors/inducers may affect total plasma risperidone concentrations with potential clinical implications [9]. In this respect, it has been reported that concomitant treatment with fluoxetine or paroxetine, selective serotonin reuptake inhibitors (SSRIs) with potent inhibitory activity on CYP2D6, may cause a significant elevation in the plasma concentrations of the active fraction of risperidone, possibly associated with occurrence or worsening of extrapyramidal side effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of risperidone were increased by fluoxetine co-administration to approximately fourfold of control, while the levels of 9-hydroxyrisperidone were not significantly affected (Spina et al 2002). The incidence of parkinsonian symptoms increased during longer-term therapy with fluoxetine.…”
Section: Risperidonementioning
confidence: 83%
“…Vários relatos confirmam que a prescrição de fluoxetina e amitriptilina/ nortriptilina pode aumentar os níveis plasmáticos da amitriptilina/nortriptilina e provocar toxicidade (delírios e convulsões). Caso não haja redução da concentração da fluoxetina − medida esta nem sempre eficaz pelo fato de a redução dos níveis de fluoxetina e norfluoxetina ocorrer de forma extremamente lenta em virtude da auto-inibição do seu metabolismo −, a redução e/ ou interrupção desse composto tende a não ser eficaz diante de uma emergência clínica (atribuiu-se morte à toxicidade crônica da amitriptilina causada pela fluoxetina) (Spina et al, 2002).…”
Section: Discussionunclassified